The triple crisis and the global aid architecture - Tony Addison; Channing Arndt; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
The global economy is passing through a period of profound change. The immediate concern is with the financial crisis, originating in the North. The South is affected via reduced demand and lower prices for their exports, reduced private financial flows, and falling remittances. This is the first crisis. Simultaneously, climate change remains unchecked, with the growth in greenhouse gas emissions exceeding previous estimates. This is the second crisis. Finally, malnutrition and hunger are on the rise, propelled by the recent inflation in global food prices. This constitutes the third crisis. These three crises interact to undermine the prosperity of present and future generations. Each has implications for international aid and underline the need for concerted action.
Keywords: F0; O1; 330; financial crisis; global food prices; climate change